MSSP: A Blockchain Sharding Protocol Based on Multi-Shard Storage - Jinyi Liu; Junfeng Tian; Zhaoyu Nian (Applied Sciences)
Sharding is currently one of the mainstream technologies for solving the scalability problem in blockchain systems. However, with the increase in shard numbers, the coordination and management of cross-shard transactions become more complex, limiting the scalability of the system. Existing methods usually split cross-shard transactions into multiple sub-transactions for processing, which not only reduces throughput but also increases transaction latency. This paper proposes a blockchain sharding protocol based on multi-shard storage to address this issue. In this protocol, nodes can store data from multiple shards, and nodes that store the same shard set form a consensus zone, which can directly handle cross-shard transactions and improve transaction processing efficiency. We propose a priority sorting mechanism to defend against double-spending attacks effectively. In addition, we introduce a P-probability return update completion proof mechanism to ensure node data consistency while enhancing blockchain security. Finally, we conduct a security analysis and performance testing of this protocol. The results show that the multi-shard storage protocol has significant advantages in terms of throughput, latency, and security compared to traditional sharding protocols.